RESEARCH ON FOREIGN INVESTORS NEEDS FOR NEW WORKFORCE IN FREE INVESTMENT ZONES IN AUTONOMOUS PROVINCE OF VOJVODINA - Damnjanović, Jelena; Stankov, Biljana; Roganović, Milijana (International Journal of Economic Practice and Policy, 2020)
As one of the most economically and culturally developed regions in the Republic of Serbia, since the beginning of the XXI century the Autonomous Province of Vojvodina (AP Vojvodina) has been a particularly attractive investment destination. Therefore, the research of the potentials and the incentives that this location is offering was very interesting for the authors of this empirical study. The subject of this research is about the identification of the needs of the foreign investors for the new workforce. The sample of the research included 18 companies owned by foregin investors that operate in the free investment zones in AP Vojvodina (Novi Sad, Zrenjanin, Subotica and Apatin). Apart from attracting foreign investments, one of the fundamental reasons for creating free investment zones in the Republic of Serbia and AP Vojvodina was the increase of employment. Therefore, the goal of this research is the analysis of foreign investors’ experiences with the jobs that were highly wanted during the research period, as well as identifying the key skills of the workers that are deemed the most important for the aforementioned jobs. With this empirical research the authors are confirming the general and specific research hypothesis and conclude that the foreign investors that have been operating in the free investment zones of the AP Vojvodina in 2018. have increased the level of employment in this region because they employed new workers with specific qualifications. Their needs for specific job positions were well-defined and clearly oriented towards several most sought-after jobs, while the certain worker skills were identified as key points for working on the newly-opened job positions.
Keywords: foreign direct investments; free investment zones; worker skills; AP Vojvodina; workforce